Strategies for expanding the lung donor pool and increasing the number of transplants in Turkey (Annals of Medical Research, 2025)
Aim: Lung transplantation is the treatment of choice in end-stage lung diseases. However, the shortage of organ donors is a significant challenge. This study analyzes lung donor characteristics and evaluates strategies to expand the donor pool in Turkey.Materials and Methods: Data from 136 cadaveric lung donors offered to our clinic between 2021 and 2023 were examinedincluding donor characteristics such as age, medical history, cause of death, and laboratory results. The donors were divided into two groups: accepted versusrejected.Results: This study evaluated 136 out of 959 deceased donors in Turkey, representing 14.1% of all deceased donors between 2021 and 2023. Fifty-three deceased donors were offered to the lung transplant clinic in 2021, 44 in 2022, and 39 in 2023. Among these, 25 donors were accepted for transplantation, and 111 were rejected .The mean age of the donors was 37.5 years. The patients in the rejected group were significantly older than the patients in theaccepted group. The most common cause of death of the deceased donors was intracranial hemorrhage. Significant differences were observed between the groups in terms of PaO₂/FiO₂ ratios were lower than 300 mm-Hg in the majority of the patients in the rejected group. Furthermore, patients in the rejected group had a higher prevalence of hypertension and a history of smoking in the rejected group.Microbial growth was observed in 22.42% of total donors, with a higher rate in the accepted group. Transoesophageal echocardiography (TOE) or transthoracic echocardiography (TTE) was used for cardiac evaluation of donor.Conclusion: The decline in donor availability and lung transplants in Turkey highlights the need for expanding donor criteria, including marginal donorsAdditionally, increasing public awareness and strengthening healthcare infrastructure are crucial to improving deceased donor organ donation rates and solid organ transplantation rates in Turkey.
Keywords: End-stage lung diseases; Lung donor; Lung transplantation; Deceased donor organ transplantation